Altitudinal variation of wild yam (Dioscorea hispida Dennst.) in Alamada, Cotabato - Bayog, Luz L. (Animo Repository, 2004)
The altitudinal distribution of Dioscorea hispida Dennst. (c.n. wild yam) was studied from March 2003 to April 2004. Together with other plant species, wild yam was collected from Mt. Akir- Akir in Barangay Pacao, and Mt. Bay-ang in Barangay Barangiran, Alamada, Cotabato. D. hispida was found to be widely distributed at the six altitudes of the two study sites. It was found to grow abundantly with hardwood trees and bamboos on moist and friable soil regardless of the altitude. The characteristic dense vegetation and close canopies in these altitudes contribute to low air and soil temperatures, which favors the growth of D. hispida. Its leaves at higher elevations were smaller, coarser, harder, and more pubescent compared with those found at the lower elevations. D. hispida plants were relatively denser in population in Mt. Akir-Akir than in Mt. Bayang. This abundance was observed particularly during the July sampling period. The data on March 11-14, 2003 sampling in Mt. Bay-ang showed that the air temperature (23.5 0C) at 400 masl and phosphorus contents (8.0 ppm, 29.4 ppm, and 80.8 ppm) significantly differed from those of other altitudes. The same parameters in Mt. Akir-Akir did not differ significantly. However, the same parameters differed significantly with those found in July 11-14, 2003 sampling. The air and soil temperatures decreased with altitude. The organic matter contents which ranged from 3.3 to 4.5 % of the two mountains were low in all altitudes. The soil was slightly acidic in all of the altitudes. Both Mt. Akir-Akir and Mt. Bay-ang predominantly had the sandy clay type of soil. D. hispida was observed to be least in number particularly at 400 masl the area of which was characterized with clay type of soil. The potassium and phosphorous contents were markedly high in both mountains. Higher yield of genomic DNA from all samples was only obtained when liquid nitrogen was used during the extraction. The restriction enzymes EcoR1, BamH1, and HindIII were used but results were not substantial to make meaningful RFLP analysis.